Pharmacokinetic Assessment of Sufentanil in Cardiac Surgery - Manfio, J. L.; Santos, L. M.; Carmona, M. J. C.; dos Santos, M. B.; Santos, S. RCJ. (Drug Research, 2013)
Plasma monitoring and pharmacokinetic assessment are important tools used in therapeutic control. Sufentanil is responsible for the hemodynamic stabilization of patients, providing better suppression of the neuroendocrine response compared to its analogue fentanyl. This study aims to use the plasma monitoring of sufentanil in patients undergoing cardiac surgery with extracorporeal circulation (ECC, group 1) or without ECC (group 2) to assess the pharmacokinetics of the compound.The 42 patients in this study received 0.5 μg/kg of sufentanil through bolus injection followed by a maintenance infusion of 0.5 μg/kg.h. Serial blood samples were collected during the post induction intraoperative period and during the postoperative period until 36 h after sufentanil administration. The plasma concentrations were determined by a validated method utilizing liquid chromatography coupled to mass spectrometry. The pharmacokinetic modeling was performed using a 3-compartment model fit.The surgical patients included in the protocol were adults of both genders, with 30 patients in the ECC group and 12 in the group without ECC. The plasma concentrations obtained were significantly different between the 2 groups. During the extracorporeal circulation procedure, intense fluctuations were observed in the sufentanil plasma concentrations. Compared with the results of group 2, the ECC procedure reduced the terminal or gamma half-life from 36.35±6.37 h to 23.25±2.75 h in group 1. In addition, the ECC procedure promoted higher fluctuations in the sufentanil plasma concentrations without causing alterations in the area under the curve, distribution volume, clearance or the distributional (alpha) and rapid elimination (beta) half-lives (t1/2α and t1/2β, respectively).
Keywords: pharmacokinetics; analgesic drugs; cardiovascular pharmacology